Faktor Risiko Keturunan Diabetes dengan Variabel Perancunya Meningkatkan Prevalensi Diabetes Tipe 2 (Studi Estimasi) - Riyanto Riyanto (Jurnal Kesehatan Metro Sai Wawai, 2017)
Background: Type 2 diabetes is a disorder that is influenced by multifactors, involving both genetic and environmental factors. Purpose: This study aims to find a large estimate of hereditary risk factors for type 2 events by controlling controlling for other confounding variables. Methods: This study used a cross sectional design analysis model estimation with the main variable heredity. The research sample of at least 249 respondents. Measurement and observation of research variables using interview and observation methods. Multivariate analysis of estimation models uses multiple logistic regression tests and calculated attributable fraction percent (AF%). Results: The results of the final multivariate modeling analysis showed heredity was associated with the incidence of type 2 Diabetes (p value 0,000), after being controlled by confounding factors for BMI, occupation, age and central obesity with ORadjusted 19.8; 95% CI: 1,911-9,459). Calculation of the potential impact size (AF%) results of the analysis obtained 48.15%. Conclusion: The estimated magnitude of respondents who have inherited risk factors is 19.8 times more likely to have diabetes than those without heredity after being controlled by confounders of BMI, occupation and age and central obesity. People with Type 2 Diabetes who have a history of diabetes, live a healthy lifestyle, so that around 48.15% of diabetes can be prevented through hereditary factors.